CONDICIONANTES DAS POSIÇÕES SOCIAIS ROMANAS: UMA LEITURA A PARTIR DE POMPÉIA - Feitosa, Lourdes M. G. C. (PHOÎNIX, 2020)
The economic dynamism of Roman society in the first c. AD led to social diversity. Status and legal differences were linked to such variables as place, time and historical context. This paper studies both the economic and legal social spectrum through the exploration of inscriptions from Pompeii, emphasizing the role of popular strata.